Paclitaxel accelerates spontaneous calcium oscillations in cardiomyocytes by interacting with NCS-1 and the InsP(3)R - Zhang, Kun (2010)
Paclitaxel (Taxol) is a microtubule-stabilizing compound that is used for cancer chemotherapy. However, Taxol administration is limited by serious side effects including cardiac arrhythmia, which cannot be explained by its microtubule-stabilizing effect. Recently, neuronal calcium sensor 1 (NCS-1), a calcium binding protein that modulates the inositol-1,4,5-trisphosphate receptor (InsP(3)R), was described as a binding partner of Taxol and as a substrate of calpain. We examined calcium signaling processes in cardiomyocytes after treatment with Taxol to investigate the basis of Taxol-induced cardiac arrhythmia. After treating isolated neonatal rat ventricular myocytes with a therapeutic concentration of Taxol for several hours live cell imaging experiments showed that the frequency of spontaneous calcium oscillations significantly increased. This effect was not mimicked by other tubulin-stabilizing agents. However, it was prevented by inhibiting the InsP(3)R. Taxol treated cells had increased expression of NCS-1, an effect also detectable after Taxol administration in vivo. Short hairpin RNA mediated knock down of NCS-1 decreased InsP(3)R dependent intracellular calcium release, whereas Taxol treatment, that increased NCS-1 levels, increased InsP(3)R dependent calcium release. The effects of Taxol were ryanodine receptor independent. At the single channel level Taxol and NCS-1 mediated an increase in InsP(3)R activity. Calpain activity was not affected by Taxol in cardiomyocytes suggesting a calpain independent signaling pathway. In short, our study shows that Taxol impacts calcium signaling and calcium oscillations in cardiomyocytes through NCS-1 and the InsP(3)R.